Penggunaan Media Flashcard untuk Meningkatkan Keterampilan Membaca Pemahaman Peserta Didik Kelas III Sekolah Dasar - Wastuti Lestari (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2020)
This research was a class action research in order to improve reading comprehension skills in lndonesian language learning through flashcard media for 3th grade elementary school student at Surakarta 2019/2020 Academic Year. The study was conducted in three cycles consisting of three meeting with stage, including planning, action, observation, and reflection. Research data collection was done by interviewing, observing reading comprehension, and document studies technique. The validity of the data used is content validity source triangulation and technique triangulation. Data analysis techniques with Mile and Hurberman’s interactive analysis models which include data collection, data reduction, data presentation, and drawing conclusions. The result of study increased from pre-action activities 21,42%, a decreased of 20% the first cycle, an increase of 40% the second cycle, and 71,42% the third cycle. Based on the result of this result of this research, concluded than reading comprehension skills in lndonesian language learning in 3th grade students had increase by implementing the flashcard media. The implication of this researh is studenets can conclude the contents of the reading and recounted.Keywords: reading comprehension skill, flashcard, learning language at elementary school